Application of Fault Stability Analysis Techniques for Design of Deep Engineering Projects - Carter, T.G.; Valley, Benoît (American Rock Mechanics Association, 2013)
Because of the potentially problematic conditions created to deep mining or civil projects by adverse fault slip behaviour, assessing what geological structures are under a critical stress state is becoming an increasingly important endeavour. This paper presents common structural geology techniques that are not widely known or regularly applied either for deep civil engineering design or for deep high stress mining, but which can have merit for risk minimization for excavation development. Several techniques are explored and guidelines for using fault mapping data and applying stress inversion approaches are presented for advancing understanding of past and current stress state – both of which are key to establishing propensity for slip on geological structures.
2023